The association between rural/urban residence status and patient-reported outcomes in individuals with Chronic Obstructive Pulmonary Disease (COPD): Protocol for a systematic review and meta-analysis - McKenzie Granata Green; Laurie L. Meschke; Thankam Sunil; Javiette Samuel; Kristina W. Kintziger; Phoebe M. Tran (PLoS ONE, 2026)
Introduction Rural residency is associated with a disproportionate burden of chronic obstructive pulmonary disease (COPD) and poorer COPD health outcomes. While increasing focus has been placed on the influence of rural/urban residence on clinical outcomes, little is known about the impact of rural versus urban residency status on patient-reported outcome measures (PROMs) in individuals with COPD, despite the use of PROMs to tailor interventions and treatments to individual patient needs. Objective The objective of this review is to synthesize evidence of a relation between rural/urban residency status and PROMs in individuals with COPD. Methods Beginning May 2025, we will search EBSCO, Elsevier, Cochrane Library, PubMed, and relevant websites to identify research published between January 1, 2012, and November 1, 2024. Two reviewers will independently screen titles, abstracts, and full texts, with a third reviewer to resolve any discrepancies. All data sources and selection management will be fulfilled and housed in the Covidence systematic review software. The primary outcome of this review is the association between rural/urban residency and PROMs in individuals with COPD. If appropriate, a meta-analysis will be conducted. Sub-group analysis will be performed by sex. Sensitivity analysis will be performed by excluding studies with “low quality” based on risk of bias assessment. Ethics and dissemination This study is exempt from institutional review as it will be a secondary analysis of published data. Results of this study are expected by September 2025 and will be disseminated in a relevant peer-reviewed journal. Trial registration Prospero registration number: CRD42024627343.